2018
DOI: 10.1074/jbc.ac118.004816
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional effects of myosin-binding protein-C phosphorylation in heart muscle are not mimicked by serine-to-aspartate substitutions

Abstract: Myosin-binding protein-C (cMyBP-C) is a key regulator of contractility in heart muscle, and its regulatory function is controlled in turn by phosphorylation of multiple serines in its m-domain. The structural and functional effects of m-domain phosphorylation have often been inferred from those of the corresponding serine-to-aspartate (Ser–Asp) substitutions, in both in vivo and in vitro studies. Here, using a combination of in vitro binding assays and in situ structural and functional assays in ventricular tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 23 publications
8
26
0
Order By: Relevance
“…It was apparent that the amino acid substitutions used to mimic phosphorylation of cMyBP-C might be completely representative of the structural changes accompanying endogenous serine phosphorylation. Indeed, a recent report suggests that this may be the case (20). Thus, to test whether destabilization of the SRX, as observed in phosphomimetic hearts, was representative of endogenously phosphorylated cMyBP-C, WT preparations were pretreated with PKA to phosphorylate myofilament targets before performing single-nucleotide turnover assays.…”
Section: Resultsmentioning
confidence: 99%
“…It was apparent that the amino acid substitutions used to mimic phosphorylation of cMyBP-C might be completely representative of the structural changes accompanying endogenous serine phosphorylation. Indeed, a recent report suggests that this may be the case (20). Thus, to test whether destabilization of the SRX, as observed in phosphomimetic hearts, was representative of endogenously phosphorylated cMyBP-C, WT preparations were pretreated with PKA to phosphorylate myofilament targets before performing single-nucleotide turnover assays.…”
Section: Resultsmentioning
confidence: 99%
“…However, one must be careful with conclusions made on Ser-to-Asp phosphomimetic molecules as it has been argued that not all effects of Ser phosphorylation are reproduced by Ser substitution with Asp. 51 In another study, the structural effects of the M-domain phosphorylation were tested in modified mouse cMyBP-C fragment C0C2 with fluorescent and spin labels placed on Cys residues in C1 (Cys248) and C2 (Ser440Cys) domains. 52 The interprobe distance distribution was quantitated with time-resolved fluorescence resonance energy transfer (TR-FRET) and dipolar electron paramagnetic resonance (DEER).…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative microscale thermophoresis measurements gave K d for complexes between cMyBP-C and S2Δ. 51 The K d for an isolated M-domain was ~40 μM, for the C1C2 ~20 μM, and for C1 linked to C2 by a flexible unrelated linker ~480 μM. This study established that although Ig domains C1 and C2 slightly improve the binding of the M-domain by a factor of ~2, the most important region providing interacting contacts with S2Δ is the M-domain itself.…”
Section: Introductionmentioning
confidence: 99%
“…The cMyBP-C protein has also been described as a modulator of length- dependent activation of myocardium in a manner independent of cTnI phosphorylation [70, 71]. Using N-terminal fragments of cMyBP-C, it was reported that the serine-to- aspartate substitution widely used to mimic phosphorylation in transgenic mice is unable to recapitulate all aspects of PKA-mediated cMyBP-C phosphorylation [72]. This is a very important consideration in interpreting future results; however, to date, no other method has been able to isolate the functional roles of phosphorylation sites of endogenous proteins, particularly in vivo .…”
Section: Introductionmentioning
confidence: 99%